Choledochal cyst: A review of 79 cases and the role of hepaticodochoduodenostomy - Biswanath Mukhopadhyay; Ram Mohan Shukla; Madhumita Mukhopadhyay; Kartik Chandra Mandal; Partha Pratik Mukherjee; Dipankar Roy; Sumitra Kumar Biswas; Kalyani Saha Basu (Wolters Kluwer Medknow Publications, 2011)
Aim : To analyze our experience of choledochal cysts. The results of complete excision of cyst and hepaticodochoduodenostomy have been analyzed in particular. Material and Methods : Period of study: January 1993 to August 2010. Apart from basic investigations, we did ultrasonography (USG) of abdomen, contrast-enhanced computerized axial tomography scan (CECT), endoscopic retrograde cholangiopancreatography (ERCP), operative cholangiogram, hepatic isotope scan (HIDA), magnetic resonance cholangiopancreatogram (MRCP) and choledochoscopy. The patients were divided into six groups according to the management done and the results analyzed. Results : The total number of cases was 79 (Male : Female = 26 : 53). The mean age of presentation was 5.18 years . The most common mode of presentation was abdominal pain in 86% cases. Types of cysts - Type I: 63; Type IV: 12; Forme fruste: 1; Caroli's disease: 1; Cyst with atresia in the lower end of common bile duct: 2. Two patients of group A (cyst excision and Roux-en-Y hepaticojejunostomy) had recurrent pain and cholangitis. One patient required revision for stricture. In group E (n=53) (excision of cyst and hepaticodochoduodenostomy), three patients developed occasional epigastric pain and they responded to omeprazole. One patient developed anastomotic stricture and was lost to follow up. One patient of cyst with biliary atresia with biliary cirrhosis died. Conclusions : In choledochal cyst, complete excision of cyst and good bilioenteric anastomosis with wide stoma should be done. Hepaticodochoduodenostomy with wide stoma is a simple, quick procedure with preservation of normal anatomy and physiology and minimum complications. It also avoids multiple intestinal anastomoses and so should be the preferred approach.